FACTORS AFFECTING MEDICATION ADHERENCE LEVEL IN DIABETES MELLITUS PATIENS: A LITERATURE REVIEW - Sutini, Kristina; Rejeki, Dwi Sarwani Sri; Wijayanti, Siwi Pramatama Mars (jfpublisher, 2023)
Introduction. Diabetes Mellitus is a disease that affects many Indonesian people. This research aims to review articles regarding factors associated with the level of adherence to diabetes mellitus treatment. Method. The data was obtained from an electronic database of Google Scholar between 2015-2021, with the keywords